Scientific information must be open - Markov, Alexander (Морфологія / Morphologia / Morfologìâ, 2010)
A Canadian researcher, Günther Eisenbach of the University of Toronto, has found that scientific articles that are publicly available online since the publication are cited much more actively even if the magazine in which they are published is in most of the scientific libraries. The sharply increased level of citation is saved even after the open access after the expiration of a certain time fall into all other articles from this magazine.